The genus Trischizostoma (Crustacea: Amphipoda: Trischizostomidae) from the Southwest Atlantic, collected by the REVIZEE Program - Freire, Pablo R.; Serejo, Cristiana S. (Zootaxa, 2004)
Based on material collected by the REVIZEE Program along the Brazilian coastline between latitudes 11 to 22 S, five species of Trischizostoma were recorded, four are known species and are herein redescribed: T. denticulatum Ledoyer, 1978, T. longirostrum Chevreux, 1919, T. raschi Boeck, 1861, T. richeri Lowry & Stoddart, 1994, and one species is new, Trischizostoma costai sp. nov. Despite the wide world distribution of the genus, this is the first record of Trischizostoma from the southwestern Atlantic.